Pengaruh Kualitas Produk, Citra Merek, dan Promosi Terhadap Minat Beli Smartphone Samsung di Kabupaten Sragen - Nadila Dwi Saputri; Ahmad Sidiq (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Competition in the smartphone industry is becoming increasingly intense, driving technology companies to seek strategies to boost sales and maintain maximum profitability. One of the efforts undertaken involves improving product quality, building a strong brand image, and implementing more effective promotional strategies. This study aims to examine the influence of product quality, brand image, and promotion on purchase intention, both partially and simultaneously. The research was conducted using a survey method with a total sample of 96 respondents, determined based on Lemeshow's formula (1996), consisting of Samsung smartphone users in Sragen Regency. Data were collected through questionnaires and measured using a Likert Scale. The data analysis was conducted using both qualitative descriptive and quantitative methods, employing SPSS version 25. The results of the study indicate that, partially: (1) product quality has a positive but not significant effect on purchase intention, (2) brand image has a positive but not significant effect on purchase intention, and (3) promotion has a positive and significant effect on purchase intention. Simultaneously, the three variables have a positive and significant influence on consumers' purchase intention.